Ascender. Volume two, The dead sea - Lemire, Jeff; Nguyen, Dustin (Image Comics, 2020)
"After a bruising escape attempt from the planet Sampson, Andy finds himself in the clutches of the militia, which means the murderous Mother can't be far behind. Meanwhile, his daughter Mila has booked passage on a ship piloted by none other than the irascible Captain Telsa. And while Vampires may rule this strange galaxy, they're no match for Kanto, the Blood Scrapper--the most badass vampire hunter in the universe!"--Provided by publisher.